2019
DOI: 10.1021/acsbiomaterials.9b01195
|View full text |Cite
|
Sign up to set email alerts
|

Bone-Seeking Albumin-Nanomedicine for In Vivo Imaging and Therapeutic Monitoring

Abstract: Malignant osteolysis associated with irreversible primary bone tumors and bone metastases remains a clinically urgent problem. Exploiting the imaging and therapy function of flexible nanomedicine can provide an alternative for therapeutic navigation and monitoring of malignant osteolysis. Here, we report the development of albumin-based gadolinium oxide nanoparticles loaded with doxorubicin and conjugated with bone-seeking alendronate for targeted delivery and therapeutic monitoring. Compared with nontargeted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Chen et al developed albumin-based gadolinium-oxide NPs (GdNPs) loaded with doxorubicin (DOX) and conjugated with bone-seeking alendronate (ALN) to treat malignant bone destruction. The abundance of tyrosine residues in the albumin molecule resulted in a high radiolabeling efficiency [ 107 ].…”
Section: Radiolabeling Of Nps With Beta-emitting Isotopesmentioning
confidence: 99%
“…Chen et al developed albumin-based gadolinium-oxide NPs (GdNPs) loaded with doxorubicin (DOX) and conjugated with bone-seeking alendronate (ALN) to treat malignant bone destruction. The abundance of tyrosine residues in the albumin molecule resulted in a high radiolabeling efficiency [ 107 ].…”
Section: Radiolabeling Of Nps With Beta-emitting Isotopesmentioning
confidence: 99%
“…SPECT/CT imaging has shown outstanding penetration capacity and is more applicable for deep tissue imaging and especially for OSA imaging [ 66 , 67 ]. A perfect option for the therapeutic management and evaluation of malignant osteolysis could be the imaging and therapy role of versatile nanomaterials [ 68 ]. Different forms of nanomedicines based on albumin have been investigated for cancer therapy, guided imaging, and biosensors [ 69 , 70 , 71 ].…”
Section: Diagnosis Of Human Osteosarcomamentioning
confidence: 99%
“…For example, an alternative to therapeutic navigation and monitoring of malignant osteolysis could be to leverage the imaging and therapy role of flexible nanomedicine. Chen et al reported the development of albumin-based gadolinium oxide nanoparticles loaded with doxorubicin and conjugated with bone-seeking alendronate for targeted delivery and therapeutic monitoring [ 68 ]. After radio labeling with 125 I and SPECT imaging, the authors observed a good distribution of NPs in the body.…”
Section: Diagnosis Of Human Osteosarcomamentioning
confidence: 99%
“…A few emerging technologies, including tissue engineering material transplantation ( Liu J. Y. et al, 2021 ), stem cell technology ( Shang et al, 2021 ), and nanomedicine ( Qiao K. et al, 2022 ), are potential means to promote the treatment of complex bone diseases. In particular, nanomedicine, based on various nanobiomaterials has significantly accelerated the diagnosis research, treatment, and regeneration of bone diseases, and has obtained numerous achievements ( Chen et al, 2020 ; Hagaman et al, 2021 ). There are a wide variety of nanobiomaterials, including carbon-based, metal-based, virus-based, lipid-based, polymer-based, liposomes, cubes, micelles, exosomes, and cell membrane coatings ( Sharma et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%